Evaluation of growth, yield and calorific value of Miscanthus x giganteus (Poaceae) biomass established in south central of Chile - Muñoz, Fernando; Cancino , Jorge; Rodríguez, Roque; Olave, Rodrigo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
Experimental crops of Miscanthus x giganteus were planted in three contrasting sites in Chile’s south central to evaluate its growth and energy potential. In the second year of growth, the crop exhibited large differences amongsites regarding height (52.1 to 158.2 cm), biomass yield (1.1 to 9.0 Mg ha-1), ash content (3.8 to 9.6%) and calorific value (16.64 to 18.14 MJ kg-1). The chemical composition of the biomass indicated cellulose 36%, hemicellulose 22.3% and lignin 26.9%. Elemental analysis indicated C and H content of 41.9% and 6.6% respectively. Therefore, Miscanthus x giganteus offers suitable attributes to be used for energy generation in Chile.